ANALISIS PERENCANAAN BUKIT BUATAN (ESCAPE HILL) TERHADAP TINGGI RUN UP UNTUK TEMPAT EVAKUASI SEMENTARA - Windy Widilestari; Munirwansyah Munirwansyah; Halida Yunita (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
As we know, there is still a lack of the optimal effort for temporary evacuation sites to face the various threats of the earthquake which may caused the tsunami in the city of Banda Aceh. To deal with this serious threat, it is necessary to prepare a place of salvation to face the tsunami. In this case, it is an escape hill. The objective of this research is to determine the bearing capacity of the subgrade to the escape hill planning and the amount of the settlement, due to the load of the embankment height (Hcrit) and the value of the slope safety factor (FK). This research is conducted in Desa Deah Baro with the GCS coordinates (Geographic Coordinate System) 5º33'45.72"N 95º17'51.34"E which was calculated by using the Plaxis 8.2 computing system on the variations of the embankment height which started from the existing which is 2,0 m height, 4,0 m, 6,0 m, 8,0 m, 10 m and 12 m (run-up performance). As the results of analysis, the researcher found that the addition of the load due to the increase in soil embankment height has resulted in an increase in the value of settlement to the soil stability with an average percentage of 2,86% and the safety factor decreasing value (FK) numbers on slopes with an average percentage of 0,10%. At 2,0 m embankment heights, the researcher obtained a settlement value of 0,271 cm with the safety factor value (FK) is 1,684 greater than 1. Furthermore, with the embankment height of 4,0 m, there is a settlement of 1,139 cm dan safety factor (FK) 1,365 greater than 1. At a embankment height of 6.0 m there is a settlement of 3,035 cm and a safety factor (FK) 1,214 greater than 1. At embankment heights of 8,0 m, the settlement is 6,244 cm with a safety factor (FK) 1,135 greater than 1. For embankment heights of 10 m and 12 m, the decrease occurred was 10,991 cm and 17,446 cm with safety factor (FK) = 1,095 and 1,044~1. The occured decline was still within the tolerance limits, so that the subgrade was still able to withstand the embankment. The results of the value of the safety factor (FK) showed that the slope was safe and did not indicate the slope slides.